Heteropathic versus homopathic resource integration and value co-creation in service ecosystems - Peters, Linda D. (Elsevier, 2016)
While the notion that resource integration is central to understanding value co-creation in service ecosystems, there is currently no clear and detailed definition of resource integration. The philosophical concept of emergence makes a clear distinction between instances of resource integration based on emergent relations between resources, here termed heteropathic resource integration, and instances of resource integration based on summative relations between resources, here termed homopathic resource integration. It is the new emergent properties that result from heteropathic resource integration that become an important factor in enhancing resourceness and thus value co-creation. Using the concept of emergence, heteropathic resource integration may lead to new emergent properties in service ecosystems, properties which may help and/or hinder the viability of service ecosystems. The assessment of the value co-created by resource integrators may be related to these new emergent properties.